Effects of kinesiotape on pain and disability in individuals with chronic low back pain: a systematic review and meta-analysis of randomized controlled trials. (April 2019) - Li, Yuejie; Yin, Ying; Jia, Gongwei; Chen, Hong; Yu, Lehua; Wu, Dandong
Objective: To explore the effects of kinesiotape on pain and disability in individuals with chronic low back pain. Data sources: PubMed, Embase and the Cochrane Central Register of Controlled Trials were searched for English language publications from inception to 13 February 2018. Review methods: This study was registered in PROSPERO (CRD42018089831). Our key search terms were ((kinesio taping) OR (kinesiotaping) OR (kinesiotape)) AND (low back pain). Randomized controlled trials evaluating the effects of kinesiotape published in English language were included in this review. The reference lists of retrieved studies and relevant reviews were also searched. Quality of the included trials was assessed according to 2015 updated Cochrane Back and Neck Review Group 13-Item criteria. Results: A total of 10 articles were included in this meta-analysis. A total of 627 participants were involved, with 317 in the kinesiotape group and 310 in the control group. The effects of kinesiotape on pain and disability were explored. While kinesiotape was not superior to placebo taping in pain reduction, either alone ( P  = 0.07) or in conjunction with physical therapy ( P  = 0.08), it could significantly improve disability when compared to the placebo taping ( P  < 0.05). Conclusion: Since kinesiotape is convenient for application, it could be used for individuals with chronic low back pain in some cases, especially when the patients could not get other physical therapy.